Utilization of Human-Like Pelvic Rotation for Running Robot - Otani, Takuya; Hashimoto, Kenji; Yahara, Masaaki; Miyamae, Shunsuke; Isomichi, Takaya; Hanawa, Shintaro; Sakaguchi, Masanori; Kawakami, Yasuo; Lim, Hun-ok; Takanishi, Atsuo (Frontiers in Robotics and AI, 2015)
The spring loaded inverted pendulum (SLIP) is used to model human running. It is based on a characteristic feature of human running, in which the linear-spring-like motion of the standing leg is produced by the joint stiffness of the knee and ankle. Although this model is widely used in robotics, it does not include human-like pelvic motion. In this study, we show that the pelvis actually contributes to the increase in jumping force and absorption of landing impact. On the basis of this finding, we propose a new model, SLIP2 (spring loaded inverted pendulum with pelvis), to improve running in humanoid robots. The model is composed of a body mass, a pelvis, and leg springs, and, it can control its springs while running by use of pelvic movement in the frontal plane. To achieve running motions, we developed a running control system that includes a pelvic oscillation controller to attain control over jumping power and a landing placement controller to adjust the running speed. We also developed a new running robot by using the SLIP2 model and performed hopping and running experiments to evaluate the model. The developed robot could accomplish hopping motions only by pelvic movement. The results also established that the difference between the pelvic rotational phase and the oscillation phase of the vertical mass displacement affects the jumping force. In addition, the robot demonstrated the ability to run with a foot placement controller depending on the reference running speed.